Arnold‐Chiari type 1 malformation in Potocki–Lupski syndrome. Issue 7 (8th May 2019) - Varon, Alberto; Whitt, Zachary; Kalika, Paige M.; Potocki, Lorraine; Barbouth, Deborah S.; Walz, Katherina
Abstract: Potocki–Lupski syndrome (PTLS) is a genetic disorder that results from an interstitial duplication within chromosome 17p11.2. Children with PTLS typically present with infantile hypotonia, failure to thrive, and global developmental delay with or without major organ system involvement. Systematic clinical studies regarding growth, cardiovascular disease, and neurocognitive profiles have been published; however, systematic evaluation of central nervous system structure by magnetic resonance imaging (MRI) of the brain has not been reported. Herein, we describe three patients with PTLS who were found—in the course of routine clinical care—to have a type 1 Arnold‐Chiari malformation (CM‐1). This finding raises the question of whether the incidence of CM‐1 is increased in PTLS, and hence, if an MRI of the brain should be considered in the evaluation of all patients with this chromosomal duplication syndrome.